2010
DOI: 10.1523/jneurosci.5249-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Complement Component C1q Mediates Mitochondria-Driven Oxidative Stress in Neonatal Hypoxic–Ischemic Brain Injury

Abstract: Hypoxic-ischemic (HI) brain injury in infants is a leading cause of lifelong disability. We report a novel pathway mediating oxidative brain injury after hypoxia-ischemia in which C1q plays a central role. Neonatal mice incapable of classical or terminal complement activation because of C1q or C6 deficiency or pharmacologically inhibited assembly of membrane attack complex were subjected to hypoxia-ischemia. Only C1q Ϫ/Ϫ mice exhibited neuroprotection coupled with attenuated oxidative brain injury. This was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 61 publications
(66 reference statements)
3
85
0
Order By: Relevance
“…Controlling for complement activation is essential because previous studies have shown that manipulation of the complement cascade can strongly alter stroke outcome in different animal species. 35,36 …”
Section: Regulatory T Cells Promote Stroke 687mentioning
confidence: 99%
“…Controlling for complement activation is essential because previous studies have shown that manipulation of the complement cascade can strongly alter stroke outcome in different animal species. 35,36 …”
Section: Regulatory T Cells Promote Stroke 687mentioning
confidence: 99%
“…C1q knockout mice show neuroprotection coupled with attenuated oxidative brain injury, and resistance to oxygen-glucose deprivation. In contrast, post-ischemic exposure to exogenous C1q increases both mitochondrial ROS production and neuronal injury [117]. C1q receptor overexpression in cells results in caspase-3 activation, mitochondrial dysfunction, and apoptosis [118].…”
Section: Cr1mentioning
confidence: 99%
“…Mitochondrial membrane potential was assayed in terms of the mitochondrial uptake of the potential-sensitive dye safranin O, as previously described (68,69). Briefly, isolated mitochondria were suspended in respiration buffer containing safranin O (1 μM).…”
Section: Mitochondrial Assaysmentioning
confidence: 99%